Cardiac malformations and midline skeletal defects in mice lacking filamin A. - Hart, A; Morgan, J; Schneider, J; West, K; McKie, L; Bhattacharya, S; Jackson, I; Cross, S (2006)
The X-linked gene filamin A (Flna) encodes a widely expressed actin-binding protein that crosslinks actin into orthogonal networks and interacts with a variety of other proteins including membrane proteins, integrins, transmembrane receptor complexes and second messengers, thus forming an important intracellular signalling scaffold. Heterozygous loss of function of human FLNA causes periventricular nodular heterotopia in females and is generally lethal (cause unknown) in hemizygous males. Missense FLNA mutations underlie a spectrum of disorders affecting both sexes that feature skeletal dysplasia accompanied by a variety of other abnormalities. Dilp2 is an X-linked male-lethal mouse mutation that was induced by N-ethyl-N-nitrosourea. We report here that Dilp2 is caused by a T-to-A transversion that converts a tyrosine codon to a stop codon in the Flna gene (Y2388X), leading to absence of the Flna protein and male lethality because of incomplete septation of the outflow tract of the heart, which produces common arterial trunk. A proportion of both male and female mutant mice have other cardiac defects including ventricular septal defect. In addition, mutant males have midline fusion defects manifesting as sternum and palate abnormalities. Carrier females exhibit milder sternum and palate defects and misshapen pupils. These results define crucial roles for Flna in development, demonstrate that X-linked male lethal mutations can be recovered from ENU mutagenesis screens and suggest possible explanations for lethality of human males hemizygous for null alleles of FLNA.